2012
DOI: 10.4048/jbc.2012.15.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Volume Analysis of Lung and Heart according to Respiration in Breast Cancer Patients Treated with Breast Conserving Surgery

Abstract: PurposeAdjuvant radiotherapy of breast cancer using a photon tangential field incurs a risk of late heart and lung toxicity. The use of free breathing (FB), expiration breath hold (EBH), and deep inspiration breath hold (DIBH) during tangential breast radiotherapy as a means of reducing irradiated lung and heart volume was evaluated.MethodsIn 10 women with left-sided breast cancer (mean age, 44 years) post-operative computed tomography (CT) scanning was done under different respiratory conditions using FB, EBH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
3
11
1
Order By: Relevance
“…Several other groups also showed significant cardiac sparing, but they did not find any lung sparing. 19,20 Shim et al 20 reported a nonsignificant reduction in lung V 20 and a trend for improved mean lung dose with DIBH, but the relative increase in lung volume with DIBH was much smaller in their study, approximately 45%, compared with 75% in our study, which may have limited their ability to detect any lung sparing. Our data suggest that accompanying a larger total lung volume, there is a significant reduction in mean lung dose and lung V 20 with DIBH.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Several other groups also showed significant cardiac sparing, but they did not find any lung sparing. 19,20 Shim et al 20 reported a nonsignificant reduction in lung V 20 and a trend for improved mean lung dose with DIBH, but the relative increase in lung volume with DIBH was much smaller in their study, approximately 45%, compared with 75% in our study, which may have limited their ability to detect any lung sparing. Our data suggest that accompanying a larger total lung volume, there is a significant reduction in mean lung dose and lung V 20 with DIBH.…”
Section: Discussioncontrasting
confidence: 74%
“…14,15,[19][20][21]23,24 Direct comparisons of these studies are challenging because of the differences in reported dose-volume histogram parameters, treatment delivery techniques, inclusion of PMRT patients, and use of RNI. Swanson et al 14 published one of the largest series of patients and showed significant reductions in the mean heart dose, HVIF, heart V 5-30 , mean lung dose, and lung V 5-20 with DIBH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this question, ECG-gated 4DCT based on breath-hold was used in this study to analyze the impacts of cardiac activity on the heart and substructures. Shim et al found that the mean value of the heart D 5 was reduced from 15.33 Gy to 5.26 Gy and that V 18 was reduced from 4.50 to 1.83 with breath-hold treatment compared with free-breathing treatment for breast cancer radiotherapy [ 18 ]. In addition, we employed MIM, a commercial software package used in clinical practice, and the algorithm of deformation image registration has been proven to have high accuracy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIP merged two types of radiation therapy in a novel way by offering “Canadian” hypo-fractionation (15–20 daily fractions) with a partial breast volume. Deep inspiration breath-hold (DIBH) was employed to reduce cardiac dose [ 22 24 ] and improve target volume coverage by immobilizing the breast and decreasing toxicity to the ipsilateral lung [ 25 ].…”
Section: Introductionmentioning
confidence: 99%